2018
DOI: 10.1111/acps.12969
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between childhood adversities and dissociation in severe mental illness: a meta‐analytic review

Abstract: The relationship between childhood adversities and dissociation in severe mental illness: a meta-analytic review Rafiq S, Campodonico C, Varese F. The relationship between childhood adversities and dissociation in severe mental illness: a metaanalytic review Objective: Several studies have observed that dissociative experiences are frequently reported by individuals with severe mental illness (SMI), especially amongst patients that report a history of adverse/traumatic life experiences. This review examined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 113 publications
2
34
1
1
Order By: Relevance
“…Existing narrative reviews have focused on the effect of CA in individuals with a positive family history of psychosis or with particular genotypes, such as specific variants of BDNF or COMT (Ayhan, McFarland, & Pletnikov, 2016;Uher, 2014), and described the interaction of CA with cannabis use and adult life events or psychosocial stressors (Beards & Fisher, 2014;Parakh & Basu, 2013;Pelayo-Teran, Suarez-Pinilla, Chadi, & Crespo-Facorro, 2012;van Winkel, Van Nierop, Myin-Germeys, & van Os, 2013;van Zelst, 2008). A role for insecure attachment styles, dysfunctional cognitive schema, reasoning biases, and non-psychotic symptoms has also been evidenced in the literature (Bebbington, 2015;Freeman & Garety, 2014;Rafiq, Campodonico, & Varese, 2018). Moreover, several mediating pathways linking CA with positive psychotic symptoms have been hypothesised, such as internal source monitoring processes and dissociation mediating the association between childhood sexual abuse and auditory verbal hallucinations, and reasoning biases and attachment insecurity mediating the relationship between neglect, parental separation, and persecutory delusions (Bentall et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing narrative reviews have focused on the effect of CA in individuals with a positive family history of psychosis or with particular genotypes, such as specific variants of BDNF or COMT (Ayhan, McFarland, & Pletnikov, 2016;Uher, 2014), and described the interaction of CA with cannabis use and adult life events or psychosocial stressors (Beards & Fisher, 2014;Parakh & Basu, 2013;Pelayo-Teran, Suarez-Pinilla, Chadi, & Crespo-Facorro, 2012;van Winkel, Van Nierop, Myin-Germeys, & van Os, 2013;van Zelst, 2008). A role for insecure attachment styles, dysfunctional cognitive schema, reasoning biases, and non-psychotic symptoms has also been evidenced in the literature (Bebbington, 2015;Freeman & Garety, 2014;Rafiq, Campodonico, & Varese, 2018). Moreover, several mediating pathways linking CA with positive psychotic symptoms have been hypothesised, such as internal source monitoring processes and dissociation mediating the association between childhood sexual abuse and auditory verbal hallucinations, and reasoning biases and attachment insecurity mediating the relationship between neglect, parental separation, and persecutory delusions (Bentall et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…bullying). Informed by previous reviews, which suggested possible moderators and mediators of the CA psychosis relationship (Ayhan et al, 2016;Beards & Fisher, 2014;Bebbington, 2015;Freeman & Garety, 2014;Parakh & Basu, 2013;Pelayo-Teran et al, 2012;Rafiq et al, 2018;Uher, 2014;van Winkel et al, 2013;van Zelst, 2008), we will investigate the effect of genetic vulnerabilities, and biopsychosocial risk factors (e.g. substance use, adult life events and prolonged social stress), as well as psychological mechanisms (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Not only are personality pathologies associated with mental illness, but childhood traumatic experiences (CTE) are also closely related to it 11 . More crucial is that the relationship between CTE and PD is extremely close, possibly together, they affected subsequent psychiatric disorders 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…Dissociation can vary from normal experience ( e.g ., absorption/day dreaming) to severe pathology characterized by detachment from body and/or reality ( e.g ., Dissociative Identity Disorder). A higher rate of pathological dissociation is found in populations exposed to childhood trauma, particularly those with resulting attachment anxiety, and in psychiatric samples (Rafiq, Campodonico, & Varese, 2018 ; Dalenberg et al, 2012 ; Kong, Kang, Oh & Kim, 2018 ; Lyssenko et al, 2017 ). Attachment anxiety typically results when caregivers are inconsistent and unpredictable; thus are not attuned or responsive to the child’s emotions.…”
Section: Introductionmentioning
confidence: 99%